Statistical analysis of work-life balance and job satisfaction: an empirical study of female employees in the cigarette industry - Rizka Lia Islamiah; Faruq Faruq (Da'wa Faculty of Islamic State University Salatiga, 2024)
The concept of work-life balance has become increasingly popular in recent years. The demands of dedicating oneself to work, managing household responsibilities, and fulfilling non-work obligations have led many modern workers to adopt work-life balance strategies to harmonize their professional and personal lives. This study aims to analyze the effect of work-life balance on job satisfaction among female employees at Pitoe Cigarette Factory, Trenggalek. The research employed a simple linear regression analysis method, using data collected from questionnaires completed by 95 female employees as samples. The results of the simple linear regression test indicated a positive relationship between work-life balance and job satisfaction, with a p-value of 0.000, which is less than the significance threshold of 0.05. This finding demonstrates that improved work-life balance can contribute to increased job satisfaction among female employees. The coefficient of determination (R²) was found to be 0.413, indicating that 41.3% of the variation in job satisfaction is explained by work-life balance. Furthermore, the study revealed that both work-life balance and job satisfaction levels were categorized as moderate, suggesting the need for greater attention to managing the balance between work and personal life. These findings are expected to provide insights for Pitoe Cigarette Factory management and other companies in designing policies that support work-life balance, ultimately enhancing job satisfaction and productivity among female employees.